Активне виявлення хворих на цукровий діабет 2-го типу як провідна складова вторинної профілактики серцево-судинних уражень - Приступюк, О. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
Analysis of newly diagnosed patients with diabetes mellitus type 2 indicates that 83% of those diagnosed with diabetes is set on the treatment of patients. At the same time, the active component of his study, HbA1c greater than 6.5% up to 16% of those tested. The latter fact points to the need to strengthen information and education in the direction of the active detection of patients with diabetes mellitus.